Fracture toughness of materials subjected to a temperature gradient - Shah, Qasim Hussain; Homma, H. (Elsevier BV, 1994)
A fracture criterion for crack initiation for nan-homogeneous materials based on mechanical properties is investigated in this paper. In this work polymethylmethacrylate (PMMA) is chosen as the test material, since it is so brittle that linear fracture mechanics (LEFM) can be applied to its fracture behavior and its material properties are susceptible to temperature. Three-point bend tests were carried out to establish the temperature dependence of fracture toughness for this material, by maintaining a uniform temperature in the specimens during the test. Further tests were made by keeping the edges of the specimen at different temperatures by subjecting the specimens to specified temperature gradients. These temperature gradients create non-homogeneous mechanical properties in PMMA specimens. Fracture toughness values obtained by temperature gradient tests remarkably increase or decrease depending upon the heating or cooling configurations of the specimens as well as on the size of the temperature gradient, in comparison with those of uniform temperature tests.